Antiviral Activity and Underlying Action Mechanism of Euglena Extract against Influenza Virus - Ayaka Nakashima (MDPI AG, 2021)
It is difficult to match annual vaccines against the exact influenza strain that is spreading in any given flu season. Owing to the emergence of drug-resistant viral strains, new approaches for treating influenza are needed. Euglena gracilis (hereinafter Euglena), microalga, used as functional foods and supplements, have been shown to alleviate symptoms of influenza virus infection in mice. However, the mechanism underlying the inhibitory action of microalgae against the influenza virus is unknown. Here, we aimed to study the antiviral activity of Euglena extract against the influenza virus and the underlying action mechanism using Madin–Darby canine kidney (MDCK) cells. Euglena extract strongly inhibited infection by all influenza virus strains examined, including those resistant to the anti-influenza drugs oseltamivir and amantadine. A time-of-addition assay revealed that Euglena extract did not affect the cycle of virus replication, and cell pretreatment or prolonged treatment of infected cells reduced the virus titer. Thus, Euglena extract may activate the host cell defense mechanisms, rather than directly acting on the influenza virus. Moreover, various minerals, mainly zinc, in Euglena extract were found to be involved in the antiviral activity of the extract. In conclusion, Euglena extract could be a potent agent for preventing and treating influenza.